O currículo do ensino médio integrado: da intenção à realização - Benfatti, Xênia Diógenes (2011)
The integrated High School genre, the EMI, created by Federal Decree # 5.154/2004, brought new dimensions to national politics on High School and Professional Education. Changes caused by the integrated subjects’ proposition contributed to the appearing of new challenges to public High Schools, to education departments and even to the Ministry of Education, caused by their requiring of both conceptual and structural definition of those teaching modalities. The investigation “The Curriculum of the Integrated High School: from intention to accomplishment” is a research which has as its main objective to analyze the integration of high school curriculum and Professional Education in three different schools, as well as to provide evaluative methodology in order to support public schools in curriculum evaluation on this modality. It is, therefore, a scientific job categorized as evaluative research, whose approach is predominantly qualitative. The chosen methodological procedure was the multiple cases study. The chosen schools present the same pattern of subjects’ proposition and are located in three Brazilian states: Ceará, Maranhão and Paraná. The used resources on the research were: students, teachers, school principals, official documents from the school and political documents of government agencies; the following evidence gathering techniques were used: documental analysis, semi-structured interviews, focus groups and observation of developed activities. The results of the investigation imply that, in the studied schools, the integration is idealized and being created in the course plans, but their practical curriculum still follow the dual model, which enables to ensure that integration needs evaluation processes that indicate to the EMI school their needs, difficulties and necessary changes in order to perform the curriculum integration proposed in the documents of the Ministry of Education. The integration requires to be discussed and experienced by teachers, who, in fact, lack the time and place for institutionalized training and analysis of their educational actions, which makes harder to perform a pedagogy that brings the integration as emphasis. The initial thesis given: the curricular integration of EMI only occurs when there is available time and space to the planning, development, rating and formation of teachers for the integration of knowledge and curriculum practices of each teaching unit; was confirmed by the data and analyses made. The research explained that the structural conditions offered to schools are very important to the exercise of integration, because without this there is no integration, just intention.